Desafios enfrentados pelos trabalhadores de saúde na utilização do tratamento diretamente observados em pacientes com tuberculose nos municípios do noroeste do Paraná - Valloto, Simone Sardeto (2016)
Tuberculosis (TB), a disease caused by Mycobacterium tuberculosis, can make various organs and / or systems, but the pulmonary form is the most common and most worrisome, since in his bacillus, it is responsible for the transmission chain maintenance disease. In the state of Paraná in 2014 the incidence of tuberculosis was 18.7 cases / 100,000 inhabitants, among the cases of pulmonary TB bacillus, 79.2% of patients were cured and 8.9% abandoned treatment. In the same year, the mortality rate was 1.2 cases / 100,000 in habitants. The Regional Health 15a healing and dropout rates were respectively 77.8% and 5.8%, these rates are lower than those recommended for the control of disease in the region. One of the strategies to increase healing and reduce abandonment is the directly observed treatment (DOT), implanted in the 15th RS in June 2012. This study aimed to analyze the performance and the TDO process of implementation of the Primary Health teams in the municipalities of the 15th Regional of Health of Paraná. This is a descriptive study with qualitative and quantitative approach, involving lifting operational and epidemiological data after implementation of the strategy Directly Observed Treatment Short Course (DOTS) in the State of Paraná. In the period June-August 2015, physicians, nurses, community health workers (CHW), endemic diseases control agent, pharmacists, dentists, assistants and nursing technicians, dental health aides or technicians, working at the Health Primary Care teams in municipalities of 15th Health Regional in state of Paraná were interviewed with reported and confirmed cases of TB in SINAN NET from January to December 2014. A questionnaire with 5 questions (01 open or dissertation and 04 with multiple choice) was applied to these professionals. "What do you understand by DOT in TB?; Does DOT is performed at the health facility you work? In what way?; Who is responsible for DOT at the Health Unit you work ?; In your opinion, what do you think of the completion of DOT in TB patient ?; What are the main difficulties in performing the DOT for TB?". The qualitative data were submitted to content analysis and the quantitative were typed in a worksheet Microsoft Excel program 2010 and analyzed by statistical software Statistica 8.0. Three hundred eight-seven professionals were interviewed with an age average of 41.2 ± 10.3 years old, where 44% of respondents worked more than 10 years in public health. Most of the interviewed professionals (93.8%) knew the definition of DOT, 84.5% have been performed the DOT at least 5 days a week. Among those who believe in HOSE 48.3% said that the main difficulty in carrying out this activity is the lack of commitment of the user to treatment, with respect to question opinionated 53.2% considered the ODD as excellent, good or necessary. In conclusion there is need for improvement of actions related to patient care with TB so that the organization and performance of health services can effectively contribute to the control of tuberculosis in the country.